I2-Promoted Deoxygenative Coupling of Indolin-3-ones with Thiols for the Synthesis of 3-Sulfenylindoles - Han, Chan Bin; Park, Hyun Cheol; Ko, Haye Min (Synthesis, 2025)
This study aims to develop a facile and efficient synthetic method utilizing iodine as a catalyst for the deoxygenative coupling of indolin-3-one derivatives with thiols. Reaction of indolin-3-ones with a range of alkane- and arenethiols with 3 mol% iodine in 2,2,2-trifluoroethanol at room temperature or 60 °C gave 3-alkylthio- or 3-arylthio-substituted indoles in 52–98% yields while reaction with arenethiols using 10 mol% iodine, 1.2 equiv sodium hydroxide in acetonitrile gave 2-(arylthio)indoline-3-ones in moderate yields. Hence, regioselective C–S bond formation, which is produced at the C2 or C3 position of indolin-3-one, was achieved, depending on the presence or absence of a base and, advantageously, without the need for a transition metal catalyst and additional synthetic steps.
Keywords: iodine; deoxygenative coupling; regioselective C–S bond formation; indolin-3-one; 3-sulfenyl indole